Taenia crassiceps Antigens Control Experimental Type 1 Diabetes by Inducing Alternatively Activated Macrophages - Espinoza-Jiménez, Arlett; De Haro, Roberto; Terrazas, Luis I. (Mediators of Inflammation, 2017)
Type 1 diabetes (T1D) is an autoimmune disease caused by the selective destruction of the pancreatic β-cells, causing inability to produce insulin. Proinflammatory cytokines such as IL-1β, IL-6, TNF-α, IFN-γ, IL-12, IL-17, and NO can be released by CD4 and CD8+ lymphocytes as well as by classically activated macrophages (CAMϕs), which are important in the development of T1D. Helminth infections have been shown to prevent T1D, mainly through Th2-biased responses and increased recruitment of regulatory cell populations. Previously, we have shown that Taenia crassiceps infection in mice significantly reduces hyperglycemia, insulitis, and the incidence of T1D. In this study, we determined whether T. crassiceps-derived products such as soluble (TcS) or excreted/secreted (TcES) antigens might have a beneficial influence on the development of experimental T1D. Treatment with different doses before or after induction of T1D was analyzed. Mice that were pretreated with TcS were unable to develop T1D, whereas those receiving TcES early after T1D induction displayed significantly reduced insulitis and hyperglycemia along with increased recruitment of alternatively activated macrophages (AAMϕs) and myeloid-derived suppressor cells (MDSCs). Finally, we examined the modulatory role of AAMϕs on T1D by depleting macrophages with clodronate-loaded liposomes, demonstrating that AAMϕs are key cells in T1D regulation.